Lexin: Swedish-Turkish Dictionary - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish-Turkish dictionary for immigrants wanting to learn Swedish. Includes commonly used words and phrases as well as words from Swedish society. Published in 2002.

Svensk-turkiskt lexikon för invandrare som vill lära sig svenska. Lexikonet omfattar vanligt förekommande ord och fraser samt samhällsord som är viktiga för den som vill orientera sig i det svenska samhället. Utgiven 2002.
Lexin: Svensk-turkiskt lexikon
Keywords: everyday life; vardagsliv; Turkey; Turkiet; lexicon; lexikon; society; samhälle; lexin; lexin; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur